ETHNIC IDENTIFICATION OF CHILDREN IN INTERNATIONAL FAMILIES: A CASE STUDY OF RUSSIAN-SPEAKING CHILDREN IN SOUTH KOREA (Journal of Oriental Studies, 2025)
In recent decades, South Korea has experienced a sustained rise in international marriages, reshaping the nation’s sociocultural landscape. While much attention has been given to multicultural families formed through marriages with women from Southeast Asia, studies on Russian-speaking women from CIS countries and their children born or raised in South Korea remain limited. This paper examines the processes of ethnic identification among these children, drawing on qualitative and quantitative data collected since 2013 through field research.Grounded in key theories of ethnic identity – Erikson’s psychosocial development, Gordon’s assimilation, Greeley’s pluralism, and Cooley’s “looking-glass self” – the study also considers prominent South Korean research on multicultural families, including the 2015 National Multicultural Families Survey. Employing a mixed-methods approach of unstructured interviews, surveys, and discourse analysis, the research reveals different patterns of ethnic identification within these families.Preliminary findings indicate that children of Russian-speaking marriage migrants often adopt situationally dependent ethnic identities. Their sense of identity is shaped by external factors (appearance, language proficiency), family dynamics (parental ethnic status, naming practices), and institutional context (education system, state policy). Adolescents who migrated with their mothers tend to develop hybrid or multicultural identities, whereas those born in Korea are more likely to assimilate into Korean society more fully. The study emphasizes the influence of the post-Soviet cultural background in shaping these identity dynamics and calls for more nuanced multicultural policies in South Korea.Keywords: ethnic identity, multicultural families, Russian-speaking migrants, interethnic marriage, South Korea, children of migrants.